Sintesis Dialdehid Alginat Melalui Reaksi Oksidasi Natrium Alginat Dengan Natrium Metaperiodat - Subur P Pasaribu; Jamaran Kaban; Mimpin Ginting; Kasmirul Ramlan Sinaga (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2017)
Synthesis of dialdehyde alginate has been done by oxidation reactions of sodium alginate with sodium metaperiodate (ratio of mol 1: 1). The formation of dialdehyde alginate as a result of oxidation are characterized by FT-IR spectroscopy with a peak absorption at 1627.92 cm-1, which is the vibration stretching C = O of functional groups from the aldehyde group resulting from the -OH group oxidation process, the absorption peak is changing its wavelength and intensity more sharply compared to initial sodium alginates. In addition, the C-O-C band (cyclic ether ) at 1033 cm-1 are reduced as a result of chains cleavage. The absorption peaks that appear at 794.67 cm-1 and 732.95 cm-1 are included in the bond CH which contributes to cleavage the bending C-C of oxidized sodium alginate.